PEMIKIRAN PENDIDIKAN ISLAM MUHAMMAD ABDUH - Fatkhur Rohman (JURNAL RAUDHAH, 2016)
This brief writing will parse the thought of Muhammad Abduh about Islamic education. Muhammad Abduh thinking about education is considered the beginning of the resurrection of the Muslims in the early 19th century. This is proven by the large number of writings he published in the magazine al-Manar and al-Urwat al-Wusqa ', so that it becomes the reference for the reformer in the Islamic world. He thought about education among islam contained in the system and structure of educational institutions, educational curricula and learning methods. According to the view of Muhammad Abduh, Islam is a religion which is a very rational, appreciate the human reason, since the intellect is the one of human potential, and Islam is highly recommend to use common sense. It is these Muhammad Abduh gives a very high award against reason and evelopment of science.